Increased Coverage of Maternal Health Services among the Poor in Western Uganda in an Output-Based Aid Voucher Scheme - Obare, Francis; Okwero, Peter; Villegas, Leslie; Mills, Samuel; Bellows, Ben (World Bank, Washington, DC, 2016)
Vouchers stimulate demand for health care services by giving beneficiaries purchasing power. In turn, health facilities’ claims are reimbursed for providing beneficiaries with improved quality of health care. Efficient strategies to generate demand from new, often poor, users and supply in the form of increased access and expanded scope of services would help move Uganda away from inequity and toward universal health care. A reproductive health voucher program was implemented in 20 western and southwest Ugandan districts from April 2008 to March 2012. Using three years of data, this impact evaluation study employed a quasi-experimental design to examine differences in utilization of health services among women in voucher and nonvoucher villages. Two key findings were a 16-percentage-point net increase in private facility deliveries and a decrease in home deliveries among women who had used the voucher, indicating the project likely made contributions to increase private facility births in villages with voucher clients. No statistically significant difference was seen between respondents from voucher and nonvoucher villages in the use of postnatal care services, or in attending four or more antenatal care visits. A net 33-percentage-point decrease in out-of-pocket expenditure at private facilities in villages with voucher clients was found, and a higher percentage of voucher users came from households in the two poorest quintiles. The greater uptake of facility births by respondents in voucher villages compared with controls indicates that the approach has the potential to accelerate service uptake. A scaled program could help to move the country toward universal coverage of maternal health care.